The Effect of Motivational Interviewing on Self-Efficacy and Life Satisfaction in Cancer Patients: A Quasi-Experimental Study - Mamur, Zeki; Güneş, Dilek (My University, 2024)
Objective: Motivational interviewing has been found to be effective in the adaptation to the disease and treatment process, especially in individuals with chronic diseases. This method has been proven to be useful in achieving behavioral change, optimizing treatment and care, and rehabilitation. This research was conducted to determine the effect of motivational interviewing on self-efficacy and life satisfaction in cancer patients. Materials and Methods: The research was completed as a quasi-trial model with pretestposttest control group, with 55 experimental and 55 control group patients. Descriptive statistics, Student's t- test, and correlation analysis tests were used for analyzing the data. Results: It was found that the self-efficacy and life satisfaction mean scores of the experimental group patients increased more than the control group, and the difference between the pretest and posttest mean scores was statistically significant (p=0.001). It was determined that there was a positive significant relationship between the self-efficacy and life satisfaction post-test mean scores of the experimental group patients (p=0.001). It was found that as self-efficacy increased, life satisfaction also increased. Conclusions: In this study, it was found that the self-efficacy and life satisfaction of cancer patients increased after motivational interviewing and there was a significant positive relationship between them.
Keywords: Self-efficacy; nursing; Cancer; life satisfaction; motivational interviewing